2018
DOI: 10.1111/jvp.12675
|View full text |Cite
|
Sign up to set email alerts
|

Albendazole treatment in laying hens: Egg residues and its effects on fertility and hatchability

Abstract: This work characterized the egg residual concentrations of albendazole (ABZ) and its sulphoxide (ABZSO) and sulphone (ABZSO ) metabolites and evaluated their effect on egg fertility and hatchability after ABZ treatments to laying hens. Seventy hens were allocated in groups: Group-1 was the control without treatment; Group-2 received a single ABZ oral dose (10 mg/kg); Group-3, -4 and -5 were treated with ABZ in medicated feed over 7 days at 10, 40, or 80 mg kg day , respectively. Eggs were analyzed to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Taking into account, the physiology of egg formation allowed us to understand why high fipronil residues were found in the egg. Like other described drugs (Donoghue et al, 1997;Marmulak et al, 2015;Moreno et al, 2018), fipronil administered to laying hens by both routes is absorbed and it reaches the ovary, follicles and oviduct. The follicles go through three phases until they become eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account, the physiology of egg formation allowed us to understand why high fipronil residues were found in the egg. Like other described drugs (Donoghue et al, 1997;Marmulak et al, 2015;Moreno et al, 2018), fipronil administered to laying hens by both routes is absorbed and it reaches the ovary, follicles and oviduct. The follicles go through three phases until they become eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish embryo exposure experiments confirmed that the developmental toxicity and teratogenic effects were displayed by ABZ itself, rather than its first metabolite albendazole sulfoxide (ABZSO 2 ) and the subsequent main metabolites albendazole sulfone (ABZSO) and albendazole-2-aminosulfone (ABZSO 2 NH 2 ) [ 7 ]. It has been proven that egg hatchability was decreased when the dose of ABZ in medicated feed was 40–80 mg/kg [ 8 ]. Residues in foods of animal origin at low concentrations are unlikely to lead directly to the toxic effects described above.…”
Section: Introductionmentioning
confidence: 99%